A study on the quality of SIRIM Sabah services and its effectiveness to help the local small medium enterprises (SMEs) / Masitah Sidik - Sidik, Masitah (2013)
The purpose of this research is to determine the quality of SIRIM Sabah services and its effectiveness to help Small Medium Enterprises (SMEs). SIRIM provided services to help Small Medium Enterprises (SMEs) such as Food Packaging Consultation, Food Machinery, Testing Services and the other services. Thus there were 120 respondents selected by the researcher to be the sample size of this research and they comprised of SMEs from food industries, construction industries, foundry and glasses industries and cosmetic business. From the finding of the research the researcher founded that there were many category of customer that used SIRIM services which different in terms of races, education level, types of business, location of business and income per month. In addition of that, the researcher also found that there were many services that SIRIM provide to help SMEs. Besides that, SIRIM actually perform the pretty work to help SMEs in Sabah and only some of them felt not satisfied with the services. Respondents also have the opportunities to give suggestion to solve their problem while using SIRIM services. Hence the objectives of this research have been achieved.